2018
DOI: 10.1002/ptr.6029
|View full text |Cite
|
Sign up to set email alerts
|

Paris saponin VII induces cell cycle arrest and apoptosis by regulating Akt/MAPK pathway and inhibition of P‐glycoprotein in K562/ADR cells

Abstract: Paris saponinVII (PSVII) is a steroidal saponin isolated from the roots and rhizomes of Trillium tschonoskii Maxim. We found that PSVII could inhibit the growth of adriamycin-resistant human leukemia cells (K562/ADR) in a dose-dependent manner. Furthermore, the molecular mechanism underlying the cytotoxicity and downregulation of P-glycoprotein (P-gp) expression by PSVII was clarified. PSVII significantly suppressed cell proliferation by cell cycle arrest in the G0/G1 phase, which was associated with an obviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 32 publications
3
7
0
Order By: Relevance
“…On the contrary, reversing the high expressions of BCRP and MRP may partially restore the sensitivity of some tumor cells to chemotherapeutics, including HCC . In our research, we found that PS VII could significantly reduce the expression of P‐gp, MRP and BCRP in a concentration‐dependent manner in HepG2/ADR cells treat with ADR, which was similar to those findings by the previous researchers, representing the increased sensitivity of PS VII to the HepG2/ADR cells to ADR. A previous study reported that P‐gp can pump out antitumor drugs from cells through an energy‐dependent mechanism, leading to the reduction of cellular drug concentration and cytotoxicity and further inducing the generation of MDR .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…On the contrary, reversing the high expressions of BCRP and MRP may partially restore the sensitivity of some tumor cells to chemotherapeutics, including HCC . In our research, we found that PS VII could significantly reduce the expression of P‐gp, MRP and BCRP in a concentration‐dependent manner in HepG2/ADR cells treat with ADR, which was similar to those findings by the previous researchers, representing the increased sensitivity of PS VII to the HepG2/ADR cells to ADR. A previous study reported that P‐gp can pump out antitumor drugs from cells through an energy‐dependent mechanism, leading to the reduction of cellular drug concentration and cytotoxicity and further inducing the generation of MDR .…”
Section: Discussionsupporting
confidence: 91%
“…In this article, the HepG2/ADR cells were treated with different concentrations of PS VII (including 0.88, 1.32, and 1.98 μM) and ADR (5 nM), which could concentration dependently reduce the proliferative ability, leading to a significantly lower IC50 value than cells treated with ADR (5 nM) alone, suggesting that PS VII reversed the drug resistance of HepG2/ADR cells toward ADR. Consistent with our result, PS VII could limit the growth of ADR‐resistant human leukemia cells (K562/ADR) in a dose‐dependent manner from the work by Yan and the colleagues . Also, Li et al observed the influenced cell viability of MCF‐7/ADR cells after treatment with PS VII, and the increased sensitivity to the cytotoxic effects of ADR .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In terms of the influence of pulchinenosides on P-glycoprotein function, 48 h exposure to pulchinenosides appeared to consistently increase P-glycoprotein expression in the LS180 cells, although the mechanism has yet to be identified. In contrast to most steroidal saponins [37] that might downregulate P-gp expression, pulchinenosides exposure leads to the upregulation of P-gp/ABCB1 state. Potential mechanisms involved within the induction of P-gp functional activity, and expression could involve the Pregnane x Receptor (PXR) [38], protein kinase C [39], and the Figure 8: RT-polymerase chain reaction analysis of multidrug resistance gene 1 mRNA in LS180 cells exposed to pulchinenosides for 48 hours (n � 3, mean ± SD).…”
Section: Discussionmentioning
confidence: 88%
“…It has been used as a traditional Chinese medicine for traumatic injuries, heat-clearing and detoxifying, and relief of swelling and long-term pain [2]. Under the development of phytochemistry, steroidal saponins have been proved to be the main chemicals in the genus Paris and present a wide range of pharmacological activities such as anti-tumor [3][4][5], anti-inflammatory [6], anti-fungal [7], hemostasis [8], and immunomodulatory [9]. Moreover, Rhizoma Paridis, documented as rhizomes of Paris polyphylla var.…”
Section: Introductionmentioning
confidence: 99%